The relationship of physical balance and energy value in sheep rations - Bell, T.D.; Richardson, D.; Hughes, J.S.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2012)
Lamb-fattening rations varying in proportions of roughage to concentrates have been studied in this project for several years. Experimental evidence shows that a ratio of 55 percent roughage and 45 percent concentrates has been most efficient in the utilization of feed nutrients. In recent years much interest has been shown by feeders in rations that are ground, mixed, and the entire ration put into a pellet. Objects of the 1953 studies: 1. To determine if a ration of corn and alfalfa hay would produce larger and more economical' gains when fed as pellets than when the bay was fed long and the corn was unground. 2. To determine if certain proportions of roughages to concentrates Were more desirable than others in the completely pelleted ration.
Keywords: Sheep; Energy; Gain; Roughages; Concentrates